Innovación de la gestión pública y su incidencia en los procesos administrativos del gobierno autónomo descentralizado del Cantón Mocache, año 2023 - Aspiazu Sánchez, Deyanira Stefany (2025)
This research project evaluates innovation in public management and its impact on the administrative processes of the Decentralized Autonomous Government of the Mocache canton during 2023. The justification for the study lies in the limitations identified in the institution's current management model, with a partial digitalization of public services that generates negative effects on response times for citizen attention, impacting administrative productivity and quality. Through the application of a mixed methodology, combining observation techniques, surveys, and interviews, the objective is to determine e-government strategies based on public innovation to optimize the institution’s management and improve the provision of services to citizens. The results reveal that innovation in the GAD of Mocache is in an initial stage, with a low level of digitalization of administrative processes and limited mastery of digital tools by officials. The need to strengthen technological infrastructure, promote training in digital competencies, and develop a networked document management system that facilitates access to information between different areas was identified. The study provides relevant information to support decision-making and the formulation of public policies aimed at institutional modernization, optimization of municipal services, and increased administrative productivity.